Sour beer formulation added with bagasse and fruit juice: probiotic potential and sensory evaluation - Ribeiro, Ana Beatriz Praia (2022)
In general, the beer fermentation process is carried out by a monoculture of Saccharomyces spp. Nevertheless, beverage variations can be obtained by cofermentation from yeasts and lactic acid bacteria (LAB), featuring sour or acidic beers. Fruits by-products are substrates rich in fibers, sugars, nutrients, and bioactive compounds, and may be used in fermentation to produce other types of food. Thus, this study aimed to evaluate the feasibility of the application of the probiotic strain Lacticaseibacillus (L.) paracasei subsp. paracasei F19 with the yeast Saccharomyces cerevisiae US-05 in the production of a sour-type beer with the addition of Spondias mombin L. (known as taperebá or cajá) bagasse and juice. The sour beer was produced on a laboratory scale through four types of formulations, according to the addition of bagasse and/or fruit juice and received two stages of fermentation: lactic (L. paracasei F19) and alcoholic (S. cerevisiae). To evaluate the probiotic strain performance, a fermentability assay in the S. mombin by-product and in the hopped wort was carried out as well as a probiotic viability assessment. For the microbial growth analysis, samples were collected during the beer fermentation and during storage and were also evaluated regarding pH, total acidity, soluble solids, specific gravity, and alcohol content. The fermentation assay revealed the successful performance of L. paracasei F19 to ferment the S. mombin bagasse in a MRS medium, reaching 9.28 log CFU/mL in 24 h. Regarding the hopped wort, the probiotic microorganism had lower viability. The bacterial strain was able to survive in the formulations and promote acidification of the medium. However, the addition of S. mombin juice and/or bagasse did not support the survival of L. paracasei F19. Only the control formulation (FC) composed of wort and hops, without the addition of extra ingredients, reached high bacterial population values, around 7.84 log CFU/mL after 28 days of production (PMA-qPCR technique). Thus, the application of S. mombin bagasse and/or juice impaired the survival of the probiotic strain in the sour beer. However, the production of a potential probiotic sour beer with L. paracasei F19 in cofermentation with S. cerevisiae US-05 with moderate alcohol content is possible and other fruit juices and/or by-products ought to be tested.